Chlorococcum sp. MM11—a novel phyco-nanofactory for the synthesis of iron nanoparticles - Subramaniyam, Vidhyasri; Subashchandrabose, Suresh Ramraj; Thavamani, Palanisami; Megharaj, Mallavarapu; Chen, Zuliang; Naidu, Ravi (Journal of applied phycology, 2015)
Green synthesis of iron nanoparticles using a soil microalga, Chlorococcum sp. MM11, and their application in chromium remediation have been investigated. Spherical-shaped nanoiron was synthesized by treating the exponentially growing culture of Chlorococcum sp. with 0.1 M iron chloride solution for 48 h and incubating it under shaking in the dark. The appearance of a yellowish brown colour indicated the biotransformation of bulk iron into nanoiron. Morphological characteristics of nanoparticles with transmission electron microscopy (TEM) and dynamic light scattering (DLS) confirmed the presence of spherical-shaped nanoiron ranging in size from 20 to 50 nm. TEM imaging also revealed the localization of nanoiron on the microalgal cell surface, inside as well as outside the cell. Fourier transform infrared spectroscopy (FTIR) analysis confirmed the involvement of carbonyl and amine bonds from polysaccharides and glycoproteins present in the algal cell wall in the bioreduction as well as capping of nanoiron. Phyco-synthesized iron nanoparticles were tested for their efficiency in reducing Cr(VI), a toxic environmental pollutant. The results showed that nanoiron reduced 92 % of 4 mg L −1 Cr(VI) to Cr(III) instantaneously, while bulk iron reduced only 25 %. Thus, iron nanoparticles with high reactivity, greater stability and environmentally benign and economically viable properties can be synthesized using phyco-nanofactories like Chlorococcum sp. MM11.